IMPLEMENTASI COMPOSITE PERFORMANCE INDEX PADA MULTI CRITERIA DECISION MAKING (MCDM) UNTUK MEMILIH LOKASI USAHA UMKM - Diana Diana (Jurnal Ilmiah Matrik, 2018)
The selection of the right location for Micro, Small and Medium Enterprises (MSMEs) will have a positive influence on the development of MSMEs and is expected to provide optimal income. The criteria used to select MSME businesses are place rental costs, availability of electricity, availability of clean water, road access, parking area, level of security, proximity to suppliers, similar business and population density of implementation. The Composite Performace Index (CPI) for choosing a location produces location 4 as the best location. In this paper, a single dimension weight sensitivity test is carried out to see the stability of the CPI by conducting trials on 6 variations in the criteria weight. The sensitivity test results that the CPI local weight stability interval is 0.01≤CPI≤0.41, where Location 4 is in the first rank position. The results of the global weight stability interval are at intervals of 0.01 ≤CPI≤ 0.21, where the results of the ranking position of all alternative business locations do not change.